Immediate compared with on-demand maternal full feeding after planned caesarean delivery: a randomised trial - Tan, P.C.; Alzergany, M.M.; Adlan, A.S.; Noor Azmi, M.A.; Omar, S.Z. (Elsevier, 2016)
Objective: To evaluate immediate compared with on-demand full maternal oral feeding after caesarean delivery. Study design: A randomised trial. Setting: Obstetric unit of a university hospital in Kuala Lumpur, Malaysia. Population: Women admitted for a planned caesarean under spinal anaesthesia. Methods: Participants were randomised to a sandwich meal served immediately on return to the ward or on-demand. Main outcome measures: Primary outcomes were patient satisfaction VAS (visual analog scale of 100 mm) on the feeding regimen and vomiting at 24 hours. Results: 453 women were initially enrolled, 395 were randomised and available for analysis. Median (full range) patient satisfaction VAS scores were 82 (15–100) versus 84 (0–100) mm, P = 0.88 and vomiting rates were 1/197 (0.5%) versus 2/198 (1.0%), P > 0.99 for immediate compared with on-demand feeding, respectively. The immediate versus on-demand arms first ate at a median of 105 (35–210) versus 165 (45–385) minutes, P < 0.001, had second meal at 5.3 (1.2–15.5) versus 5.8 (2.2–29.7), P < 0.001, flatus passage at 9.5 (3.1–29.0) versus 10.3 (2.8–24.6), P = 0.023 hours post-caesarean and opiate analgesia use was 10/197 (5.1%) versus 23/198 (11.6%), P = 0.028, RR 0.4 (95% CI 0.2–0.9), NNTb 16 (95% CI 8–89). The median visual numerical rating scale (0–10 scale) for nausea and bloating at 8, 16 and 24 hours was similarly scored at zero in both arms. Other outcomes were similar. Conclusion: Immediate full feeding has some advantage over on-demand feeding. Both regimens are tolerated well. Patients probably should be fed as soon as practicable after a caesarean. Tweetable abstract: Full maternal oral feeding should commence as soon as practicable after an uncomplicated caesarean section.